If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 = x + -1 + 5x Reorder the terms: 5 = -1 + x + 5x Combine like terms: x + 5x = 6x 5 = -1 + 6x Solving 5 = -1 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 5 + -6x = -1 + 6x + -6x Combine like terms: 6x + -6x = 0 5 + -6x = -1 + 0 5 + -6x = -1 Add '-5' to each side of the equation. 5 + -5 + -6x = -1 + -5 Combine like terms: 5 + -5 = 0 0 + -6x = -1 + -5 -6x = -1 + -5 Combine like terms: -1 + -5 = -6 -6x = -6 Divide each side by '-6'. x = 1 Simplifying x = 1
| 14x=12x-64 | | 33x=-1551 | | 9(x+8)-56= | | 2.25x+.750=3.0 | | 3g-5g+11=17 | | 5+3(x+1)=35 | | -21m=-651 | | (3x+10)(x-20)=0 | | 4n=372 | | 1.8x=.4 | | P=2x(-x+2) | | 16y^3=9x^2 | | k-88=-16 | | -d+2=5 | | 48=58-p | | 7+6x(x)=4*2+x*2 | | 3(y+4)=x | | x+1/9=-4/3 | | -5c+2=-13 | | 16-x=x+36 | | 3003+x-x=7817 | | 6k-k+1=-2+-2k+30 | | 3003-x+x=7817 | | 4y-x-4=0 | | 8.1r-7.6=-18.4+2.7r | | 11(11x+7)=12(-12+9x) | | 4(w-11)-24=-3(w-2)-5-2w | | t+7t=64 | | 10z-9=3 | | 0.4x-5=-6.5 | | 49=-3j-4j | | 2x+x+3=x+2-5 |